1D charge density wave in the hidden order state of URu2Si2 - Edwin Herrera (Nature Portfolio, 2021)
URu2Si2 is known to exhibit a lower temperature phase transition termed a ‘hidden order’ due to the difficulty its detection using conventional solid-state probes and the exact mechanism still remains unknown. Here, the authors use scanning tunnelling microscopy to reveal a 1D charge density wave for cleaved samples of URu2Si2 and demonstrate a potential connection with the hidden order state.